2020
DOI: 10.1111/jch.13893
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of co‐administered telmisartan/amlodipine and rosuvastatin in subjects with hypertension and dyslipidemia

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…To the best of our knowledge, this metanalysis also studies rosuvastatin's effect on BP variability based on newer randomized control trials which were not included in previously studied metanalyses. 40,42,47,70 Heterogeneity in our studies was found to be significant in terms of efficacy of statins on variability of SBP (I 2 = 93%; p < .00001) and DBP (I 2 = 81%; p < .00001). The possible reasons for this heterogeneity can be explained by the methodological differences of the different studies; the existence of a large number of studies; a large population size, where it was also observed that the population belonged to different ethnic backgrounds; and comorbidities such as diabetes, COPD, and so forth, were found in limited studies as well as in concomitant therapies F I G U R E 5 Meta-analysis of the impact of statins on DBP, studies were sub-grouped based on concomitant BP-lowering medications.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…To the best of our knowledge, this metanalysis also studies rosuvastatin's effect on BP variability based on newer randomized control trials which were not included in previously studied metanalyses. 40,42,47,70 Heterogeneity in our studies was found to be significant in terms of efficacy of statins on variability of SBP (I 2 = 93%; p < .00001) and DBP (I 2 = 81%; p < .00001). The possible reasons for this heterogeneity can be explained by the methodological differences of the different studies; the existence of a large number of studies; a large population size, where it was also observed that the population belonged to different ethnic backgrounds; and comorbidities such as diabetes, COPD, and so forth, were found in limited studies as well as in concomitant therapies F I G U R E 5 Meta-analysis of the impact of statins on DBP, studies were sub-grouped based on concomitant BP-lowering medications.…”
Section: Discussionmentioning
confidence: 73%
“…Along with other known statins, our analysis also studies rosuvastatin, which has been shown to significantly improve BP in patients with hypertension. To the best of our knowledge, this metanalysis also studies rosuvastatin's effect on BP variability based on newer randomized control trials which were not included in previously studied metanalyses 40,42,47,70 . Heterogeneity in our studies was found to be significant in terms of efficacy of statins on variability of SBP (I 2 = 93%; p < .00001) and DBP (I 2 = 81%; p < .00001).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Hypertension and dyslipidemia have become important factors affecting the life process of the elderly 10 . Previous cross-sectional studies have found a biological correlation between dyslipidemia and hypertension 11,12 ,and dyslipidemia can increase the incidence of hypertension in people with normal blood pressure 13,14 . A randomized controlled trial showed that patients with hypertension had higher lipid levels.…”
Section: Discussionmentioning
confidence: 95%
“…The present work described a validated reverse phase HPLC method for determination of TEL, ROS, and AML in synthetic mixture used in the management of hypertension with dyslipidemia. 14…”
Section: Aimmentioning
confidence: 99%